Ultrasonic/microwave-assisted extraction of polysaccharides from Camptotheca acuminata fruits and its antitumor activity. (15th February 2019) - Sun, Haiyao; Li, Chunying; Ni, Yujiao; Yao, Liping; Jiang, Hongwei; Ren, Xueting; Fu, Yujie; Zhao, Chunjian
Highlights: An efficient UMAE procedure for extraction of CAFP was developed. The UMAE procedure provided higher yields of CAFP in a shorter time. CAFP at suitable dose is effective on H22 murine hepatoma strains in vivo. CAFP significantly inhibited the proliferation of KB, BXCP-3 and SGC-7901 cells. Abstract: In the present study, an efficient ultrasonic/microwave-assisted extraction (UMAE) procedure for the polysaccharides from the fruit of Camptotheca acuminata (CAFP) was investigated and optimized. Under the optimum conditions (ratio of liquid to raw material 30 mL/g, microwave irradiation time of 20 min, microwave irradiation power of 570 W and a fixed ultrasonic power of 50 W obtained by the response surface analysis with Box-Behnken design, satisfactory yields of CAFP (6.81 ± 0.04%) were achieved. The development UMAE technique produced higher yields in a shorter time than conventional hot water extraction (HWE): 20 vs. 120 min. In addition, in vivo CAFP at suitable dose is effective on H22 murine hepatoma strains, and CAFP significantly inhibited the proliferation of human oral carcinoma KB, pancreatic carcinoma BXCP-3 and gastric carcinoma SGC-7901 cells in vitro, indicating CAFP might be suitable for nature antitumor therapeutic agent development.